A GLOBAL APPROACH TO TEACHING NEAR-FIELD ANTENNA MEASUREMENTS - Picard, D. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A complete set of experiments on near-field antenna measurements is presented. This labwork serves two purposes: first, it introduces students to the difficulties associated with such a measurement technique, and second, they gain the confidence to work in high tech, elaborate environments. The technical goal in this labwork is to obtain the radiation pattern of an antenna through measurements of the near-field using a complete experimental set-up driven by a Macintosh computer, and performing a near-to-far field transformation using a combination of Helmholtz equation and the Fourier Transform. Actually, the knowledge students acquire in this labwork is built up in stages which are both independent and experiments in their own right: they are described in detail in the paper, along with the knowledge built up at each stage by students as they advance into the labwork, and the objectives achieved. [Vol. 8, No. 1, (1993), Special Issue on Computer Applications in Electromagnetics Education, pp 66-76]